Expectancy modulates pupil size during endogenous orienting of spatial attention. (May 2018) - Dragone, Alessio; Lasaponara, Stefano; Pinto, Mario; Rotondaro, Francesca; De Luca, Maria; Doricchi, Fabrizio
Abstract: fMRI investigations in healthy humans have documented phasic changes in the level of activation of the right temporal-parietal junction (TPJ) during cued voluntary orienting of spatial attention. Cues that correctly predict the position of upcoming targets in the majority of trials, i.e., predictive cues, produce higher deactivation of the right TPJ as compared with non-predictive cues. Since the right TPJ is the recipient of noradrenergic (NE) innervation, it has been hypothesised that changes in the level of TPJ activity are matched with changes in the level of NE activity. Based on aforementioned fMRI findings, this might imply that orienting with predictive cues is matched with different levels of NE activity as compared with non-predictive cues. To test this hypothesis, we measured changes in pupil dilation, an indirect index of NE activity, during voluntary orienting of attention with highly predictive (80% validity) or non-predictive (50% validity) cues. In agreement with current interpretations of the tonic/phasic activity of the Locus Coeruleus-Norepinephrinic system (LC-NE), we found that the steady level of cue predictiveness that characterised both the predictive and non-predictive conditions caused, across consecutive blocks of trials, a progressive decrement in pupil dilation during the baseline-fixation period that anticipated the cue period. With predictive cues we observed increased pupil dilation as compared with non-predictive cues. In addition, the relative reduction in pupil size observed with non-predictive cues increased as a function of cue-duration. These results show that changes in the predictiveness of cues that guide voluntary orienting of spatial attention are matched with changes in pupil dilation and, putatively, with corresponding changes in LC-NE activity.